Triglyceride-independent associations between circulating levels of apolipoprotein C-III and biomarkers of inflammation - Dídac Llop; Pere Rehues; Silvia Paredes; Montse Guardiola; Josefa Girona; Roser Rosales; Yaiza Esteban; Lluís Masana; Daiana Ibarretxe; Joan-Carles Vallvé; Josep Ribalta (Cardiovascular Diabetology)
Abstract Backgrounds and aims Preclinical studies suggest that a triglyceride (TG)-independent proinflammatory action of apolipoprotein C-III (apoCIII) exists. We aimed to investigate the relationship between circulating apoCIII levels and subclinical inflammation markers across different cohorts with distinctive inflammatory patterns: patients with metabolic disorders (MDs), patients with rheumatoid arthritis (RA), and controls. Specifically, we assessed the associations of apoCIII with acute inflammation biomarkers (e.g., high sensitivity C-reactive protein (hsCRP)) and novel systemic inflammation biomarkers (e.g., glycosylated proteins: Glyc-A, Glyc-B, Glyc-F), aiming to understand the role of apoCIII beyond its traditional function in TG metabolism. Methods This cross-sectional study involved 1242 participants: 906 patients with MD (metabolic syndrome, type 2 diabetes (T2DM) and/or obesity), 192 patients with RA, and 144 controls. ApoCIII and hsCRP levels were measured via immunoturbidimetric assays, and glycosylated proteins were quantified via 1 H-NMR spectroscopy. Correlation and multivariate linear regression analyses were conducted. Results ApoCIII levels were significantly and positively associated with Glyc-A, Glyc-B, and Glyc-F levels across all cohorts. Most of these associations remained significant in the MD group after adjusting for TG levels. Conversely, negative associations were detected between apoCIII and hsCRP patients with MD and RA, which were maintained after including TG in the models. Conclusion In patients with MD and RA, circulating apoCIII levels were positively associated with glycoproteins and negatively with hsCRP, in a TG-independent manner. Our results suggest that apoCIII is associated with the low-grade inflammatory profile represented by glycoproteins, independent of triglyceride levels. Additionally, we observed a negative association with hsCRP, which, while seemingly paradoxical, has been reported in previous studies.